2009
DOI: 10.1016/j.trstmh.2008.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of Strongyloides stercoralis in faecal samples using real-time PCR

Abstract: A real-time PCR method targeting the small subunit of the rRNA gene was developed for the detection of Strongyloides stercoralis DNA in faecal samples, including an internal control to detect inhibition of the amplification process. The assay was performed on a range of well-defined control samples (n=145), known positive faecal samples (n=38) and faecal samples from a region in northern Ghana where S. stercoralis infections are highly endemic (n=212), and achieved 100% specificity and high sensitivity. The us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
287
1
16

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 294 publications
(323 citation statements)
references
References 20 publications
5
287
1
16
Order By: Relevance
“…Nucleic acid tests complement non-molecular methodologies for the diagnosis of S. stercoralis, and allow the use of refrigerated, frozen, or preserved specimens 11,19,20 . This simplifies specimen transportation, particularly where collection occurs some distance from the testing laboratory, and there is no risk of laboratoryacquired strongyloidiasis 21 .…”
Section: Nucleic Acid Testsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nucleic acid tests complement non-molecular methodologies for the diagnosis of S. stercoralis, and allow the use of refrigerated, frozen, or preserved specimens 11,19,20 . This simplifies specimen transportation, particularly where collection occurs some distance from the testing laboratory, and there is no risk of laboratoryacquired strongyloidiasis 21 .…”
Section: Nucleic Acid Testsmentioning
confidence: 99%
“…the 18S rRNA small subunit (SSU); the internal transcribed spacer region 1 (ITS-1); the 28S rRNA gene; or the cyclooxygenase gene (cox1) 19,[23][24][25][26][27][28][29][30][32][33][34][35][36][37] . Published sensitivities and specificities for…”
Section: Pcrmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, PCR has been associated with higher sensitivity than classical parasitological methods during infections with lower intensity (Wongratanacheewin et al 2001). Verweij et al (2009) evaluated the molecular diagnosis of S. stercoralis in faecal samples using real-time PCR. The authors demonstrated that this methodology could be a useful alternative to the commonly used Baermann method, offering a two-fold increase in the detection rate.…”
mentioning
confidence: 99%